Psychosocial Adjustment and Mental Distress Associated With In-Game Purchases Among Japanese Junior High School Students - Shinkawa, Hiroki; Irie, Tomonari; Tanaka, Masanori; Yokomitsu, Kengo (Frontiers in Psychology, 2021)
In-game purchases, including microtransactions and loot box spending, are the monetization systems of free-to-play online games. Although some studies have suggested that excessive in-game purchases increase the risk of psychosocial maladjustment and mental distress as well as predict future problematic gaming and gambling practices, empirical studies on problematic behavioral patterns related to in-game purchasing among adolescents are lacking. This study sought to explore whether knowing the style of in-game purchases (non-purchase, planned purchase, or unplanned purchase) could be useful when characterizing maladaptive behavior among adolescents from the perspective of psychosocial adjustment and mental distress. A total of 335 junior high school students (aged 12–15 years) participated in the survey and completed a questionnaire assessing daily online gaming usage, in-game purchases, psychosocial adjustment, and mental distress. The results showed that (1) 30.7% of students had previously made in-game purchases, and at least 14.0% had made unplanned in-game purchases; (2) 19.2% of the users who had made unplanned purchases had spent greater than or equal to their actual monthly allowance within the past month, and (3) unplanned purchase gamers exhibited more behavioral problems and peer problems regarding psychosocial adjustment compared to planned purchase gamers, and more overall difficulties compared to non-purchasers. Meanwhile, more hyperactivity/inattention was seen among in-game purchasers compared to non-purchasers, regardless of whether the purchase was planned or unplanned. These findings support that understanding whether adolescents make unplanned in-game purchases could be a useful approach to describing the characteristics of online gamers with maladaptive tendencies.